2014
DOI: 10.3390/pharmacy2020161
|View full text |Cite
|
Sign up to set email alerts
|

The Production of a Framework of Competences for Pharmacy Practice in the European Union

Abstract: Abstract:The goal of the PHAR-QA (quality assurance in European pharmacy education and training) project is the production of a European framework for a quality assurance system based on competences for pharmacy practice. The PHAR-QA framework will be European, consultative and will encompass the various aspects of pharmacy practice. In this review, we describe the methodology to be used in the project and the first stage in the development of this framework. Using the proposals for competences produced by our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…The finding is in consonance with similar evidence from the field of medicine that demonstrates the relevance of the Canadian CanMEDS Physician Competency Framework to medical practice in the Netherlands [ 51 ], Denmark [ 52 , 53 ] and Australia [ 54 ]. It is also in line with evidence from studies that show consensus between countries in Europe on the relevance of a core set of competencies for pharmacy education and practice [ 42 , 55 ].…”
Section: Discussionsupporting
confidence: 86%
“…The finding is in consonance with similar evidence from the field of medicine that demonstrates the relevance of the Canadian CanMEDS Physician Competency Framework to medical practice in the Netherlands [ 51 ], Denmark [ 52 , 53 ] and Australia [ 54 ]. It is also in line with evidence from studies that show consensus between countries in Europe on the relevance of a core set of competencies for pharmacy education and practice [ 42 , 55 ].…”
Section: Discussionsupporting
confidence: 86%
“…A review of the competencies from PHARMINE and PHAR-QA was performed whereby relevant competencies such as leadership, good documentation skills and other professional skills were identified, extracted and adapted for this research competency from all sources. The competencies collected were compared to already implemented frameworks including the study of Atkinson and team, the Phar-QA project and European legislation (Atkinson et al, 2014,).…”
Section: Development Of the Toolmentioning
confidence: 99%
“…10,15 Other organisations have also developed regional, national, and institutional frameworks that map the expectations for pharmacy practice in the specified region or country. [23][24][25][26][27] A 2015 survey of 48 countries across the six World Health Organization (WHO) regions, showed that competency frameworks in pharmacy were either already in use or being developed in approximately 60% of the countries surveyed. 28 Pharmacy-related competency frameworks generally comprise competencies grouped into clusters (or domains), and sub-divided into respective behavioural indicators (or behaviours).…”
Section: Introductionmentioning
confidence: 99%